Association between cervical disorders and adverse obstetric outcomes: A retrospective cohort study - Sun, Hanxiang; Su, Xiujuan; Liu, Yang; Huang, Shijia; Liu, Xiaosong; Li, Guohua; Du, Qiaoling (Frontiers in Medicine, 2022)
Objective The purpose of this study was to explore the association of cervical disorders on obstetric outcomes of singleton pregnancies in China. Methods This hospital-based retrospective cohort study of women with live singleton births included 71,097 Chinese women. We compared the risk of adverse obstetric outcomes in different types of pregnancies with cervical disorders with those with normal cervix. Logistic regression model was used to estimate the association between cervical disorders and adverse obstetric outcomes. Results Women with cervical disorders had a higher risk of premature delivery (10.98 vs. 4.41%), preterm premature rupture of membranes (PPROM) (3.48 vs. 1.62%), low birth weight (LBW) (7.62 vs. 2.92%) and very low birth weight (VLBW) (2.01 vs. 0.28%) than women with normal cervix. After adjusting for confounding factors, compared with women with normal cervix, women with high-grade abnormal cervical cytology are at greater risk of premature birth (adjusted OR 1.971, 95% CI: 1.302–2.983), premature rupture of membranes (PROM) (adjusted OR 1.379, 95% CI: 1.047–1.815), LBW (adjusted OR 1.790, 95% CI: 1.059–3.025), and VLBW (adjusted OR 4.519, 95% CI: 1.662–12.292) than women with low-grade abnormal cervical cytology, and women with abnormal cervical cytology after treatment had a higher risk of premature birth (adjusted OR 2.060, 95% CI: 1.348–3.147), PROM (adjusted OR 1.381, 95% CI: 1.038–1.839), PPROM (adjusted OR 1.995, 95% CI: 1.022–3.892), LBW (adjusted OR 1.801, 95% CI: 1.046–3.102), and VLBW (adjusted OR 4.868, 95% CI: 1.788–13.255) than untreated women. Conclusions Our research showed that pregnant women with cervical disorders were more likely to have premature delivery, PPROM, LBW, and VLBW. Moreover, pregnant women with high-grade abnormal cervical cytology and abnormal cervical cytology after treatment had a higher risk of premature birth, PROM, LBW, and VLBW.